Safety, reactogenicity, and immunogenicity of a 2-dose Ebola vaccine regimen of Ad26.ZEBOV followed by MVA-BN-Filo in healthy adult pregnant women: study protocol for a phase 3 open-label randomized controlled trial - Karita, Etienne; Nyombayire, Julien; Ingabire, Rosine; Mazzei, Amelia; Sharkey, Tyronza; Mukamuyango, Jeannine; Allen, Susan; Tichacek, Amanda; Parker, Rachel; Priddy, Frances; Sayinzoga, Felix; Nsanzimana, Sabin; et al. (Current controlled trials in cardiovascular medicine, 2022)
Background Risks to mother and fetus following Ebola virus infection are very high. Evaluation of safety and immunogenicity of non-replicating Ebola vaccine candidates is a priority for use in pregnant women. This is the protocol for a randomized, open-label, single-center phase 3 clinical trial of the safety, reactogenicity, and immunogenicity of the 2-dose Ebola vaccine regimen in healthy adult pregnant women. This 2-dose regimen has been shown to be safe, judged effective, and approved in non-pregnant populations. Methods A total of 2000 adult (≥ 18 years of age) pregnant women will be enrolled from antenatal care facilities in Western Rwanda and randomized (1:1) to receive the 2-dose Ebola vaccine regimen (Ad26.ZEBOV, MVA-BN-Filo (group A)) or control (unvaccinated pregnant women (group B)). The primary objectives are to (1) assess adverse maternal/fetal outcomes in randomized pregnant women up to 1.5 months after delivery and (2) assess adverse neonatal/infant outcomes in neonates/infants born to randomized women up to 3.5 months after birth. The frequency and relatedness of all serious adverse events in women and newborns from randomization or birth, respectively, until study end will be reported. The reactogenicity and unsolicited adverse events of the 2-dose Ebola vaccine regimen in all vaccinated pregnant women (group A) will be reported. We will also assess the immunogenicity of the 2-dose Ebola vaccine regimen in 150 pregnant women who are anticipated to receive both vaccine doses within the course of their pregnancy (a subset of the 1000 pregnant vaccinated women from group A) compared to 150 non-pregnant women vaccinated after delivery (a subset of group B). The persistence of maternal antibodies in 75 infants born to women from the group A subset will be assessed. Exploratory analyses include assessment of acceptability of the 2-dose Ebola vaccine regimen among group A and assessment of maternal antibodies in breast milk in 50 women from group A and 10 controls (women from group B prior to vaccination). Discussion This study is intended to support a label variation to relax restrictions on use in pregnant women, a vulnerable population with high medical need. Trial registration Clinicaltrials.gov NCT04556526 . September 21, 2020.